Pengaruh Promosi Kesehatan dan Teknologi Tepat Guna Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri di SMP Negeri Tandam Hulu 1 - Hasibuan, Nazlia Rahmadiana; Girsang, Bina Melvia (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2023)
Information from the Indonesian Ministry of Health in 2013, data obtained on the number of breast cancer cases was 819 and the number of deaths was 217. There is a lack of public awareness of breast cancer detection so that every year breast cancer cases increase. The aim of the research for students is to increase knowledge and skills through BSE training for Young Women. The activity was carried out at SMP N 3 Tandam Hulu 1 for young women aged 13 to 15 years totaling 55 female students. The research used the form of outreach activities, providing material about breast cancer and awareness training. The measurements carried out provided a questionnaire as a measuring tool. The method used is a measuring instrument that provides pre-test and post-test questionnaires to measure the level of knowledge and skills of young women in BSE training.